Something is killing the children. Volume three - Tynion, James, IV (BOOM! Studios, 2021)
"As the House of Slaughter arrives to clean up the situation by any means necessary, Erica will find that the true threat to those around her isn't who - or what - she ever expected. And the cost of saving the day may be too high for anyone to pay..."--Amazon.